2021
DOI: 10.1007/s00109-021-02114-x
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in multiple-myeloma patients: cellular and humoral immunity against SARS-CoV-2 in a short- and long-term view

Abstract: Multiple myeloma patients are often treated with immunomodulatory drugs, proteasome inhibitors, or monoclonal antibodies until disease progression. Continuous therapy in combination with the underlying disease frequently results in severe humoral and cellular immunodeficiency, which often manifests in recurrent infections. Here, we report on the clinical management and immunological data of three multiple-myeloma patients diagnosed with COVID-19. Despite severe hypogammaglobulinemia, deteriorated T cell counts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Indeed their co-occurrence might reasonably enhance COVID-19 severity. Bronchiectasis had already been included in proposed models of disease severity prediction (28), and also oncologic and onco-hematologic diseases that might broaden the risk for infectious (including opportunistic) complications, as for the immunoparesis in MM (18)(19)(20)29). Compared to the above mentioned, however, the advantage of hypogammaglobulinemia is the possibility of promptly restoring and keeping normal IgG serum levels by IgRT (30).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed their co-occurrence might reasonably enhance COVID-19 severity. Bronchiectasis had already been included in proposed models of disease severity prediction (28), and also oncologic and onco-hematologic diseases that might broaden the risk for infectious (including opportunistic) complications, as for the immunoparesis in MM (18)(19)(20)29). Compared to the above mentioned, however, the advantage of hypogammaglobulinemia is the possibility of promptly restoring and keeping normal IgG serum levels by IgRT (30).…”
Section: Discussionmentioning
confidence: 99%
“…Next, we focused on variant-specific T cell responses 1–3 months after the booster vaccination. Previously, we hypothesized that T cell responses might be necessary in patients with B cell deficiency to achieve a maximal vaccination response ( von Metzler et al., 2021 ). However, after the second dose of vaccine, we reported abrogated T cell responses in patients with MM compared with healthy individuals ( Enβle et al., 2022 ).…”
mentioning
confidence: 99%
“…Statistical analysis data indicate that non-infectious conditions, such as diabetes and cancers, have numerous cases worldwide (30). Among cancer cases, the tumor microenvironment may be altered via depositing metabolites as a result of reduced immunity (31), possibly causing increased risk of infections including SARS-CoV-2 (32). It is presently reported that the COVID-19 pandemic and uncertain SARS-CoV-2 variants are still persisting and evolving diffusely.…”
Section: Discussionmentioning
confidence: 99%